Low 2018/19 vaccine effectiveness against influenza A(H3N2) among 15-64-year-olds in Europe: exploration by birth cohort - Kissling, Esther (2019)
Introduction: Influenza A(H3N2) clades 3C.2a and 3C.3a co-circulated in Europe in 2018/19. Immunological imprinting by first childhood influenza infection may induce future birth cohort differences in vaccine effectiveness (VE). Aim: The I-MOVE multicentre primary care test-negative study assessed 2018/19 influenza A(H3N2) VE by age and genetic subgroups to explore VE by birth cohort. Methods: We measured VE against influenza A(H3N2) and (sub)clades. We stratified VE by usual age groups (0–14, 15–64, ≥ 65-years). To assess the imprint-regulated effect of vaccine (I-REV) hypothesis, we further stratified the middle-aged group, notably including 32–54-year-olds (1964–86) sharing potential childhood imprinting to serine at haemagglutinin position 159. Results: Influenza A(H3N2) VE among all ages was −1% (95% confidence interval (CI): −24 to 18) and 46% (95% CI: 8–68), −26% (95% CI: −66 to 4) and 20% (95% CI: −20 to 46) among 0–14, 15–64 and ≥ 65-year-olds, respectively. Among 15–64-year-olds, VE against clades 3C.2a1b and 3C.3a was 15% (95% CI: −34 to 50) and −74% (95% CI: −259 to 16), respectively. VE was −18% (95% CI: −140 to 41), −53% (95% CI: −131 to −2) and −12% (95% CI: −74 to 28) among 15–31-year-olds (1987–2003), 32–54-yearolds (1964–86) and 55–64-year-olds (1954–63), respectively. Discussion: The lowest 2018/19 influenza A(H3N2) VE was against clade 3C.3a and among those born 1964–86, corresponding to the I-REV hypothesis. The low influenza A(H3N2) VE in 15–64-year-olds and the public health impact of the I-REV hypothesis warrant further study.